Study of Productivity Analysis of Digging Loading in Gravel Mining in PT. Galuh Cempaka Districts Cempaka City Banjarbaru South Kalimantan Province - Usman, Usman; Fanani, Yazid; Widiatmoko, Fajar Rizki (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
Galuh Cempaka Ltd. is a Gravel Mining Company with an area of 2,994 Ha. The mining system was surface mine or open pit. There are several things which should move in dig and load activities, such as mechanical soil, productivity, and compatibility of loading and conveying equipment are important factors in gravel mining activities. It influences on how far to know the effective work hour and the productivity. The purpose of this research was to determine work efficiency in Galuh Cempaka Ltd, and calculate the productivity of each equipment and the Match Factor value of the loading and conveying equipment in mining activity. From the observation and data processing, it obtained 1 unit of excavator Komatsu PC 400LC, wasingplan as far as 1.5 km. The effective work time was obtained work efficiency of 0.82 and after it was conducted the efficiency become 0.83 and it was reduced the obstacles from excavator CAT 320D. Before digging toll productivity got optimizing from CAT 320D in gravel excavation, it got 94.2 tons/hour and after it got optimizing from CAT 320D excavator in gravel excavation, it obtained 99.6 tons/hours and the IVECO 380 dump truck for gravel loading was 125.55 tons /hour. It obtained Match Factor Overburden (08) 1. it means it is less than 1. So, there was waiting time for transportation equipment which had not arrived yet. Match Factor Gravel (1.2) 1 means more than 1. So, there was a waiting time for transportation because the digging tool was filled.